Financing livestock raising with profit sharing and insurance: IPSR Innovation Profile - Ambler, Kate; Bakhtiar, M. Mehrab; de Brauw, Alan (CGIAR System Organization, 2024)
This product provides finance for cattle fattening through a profitsharing model. Eligible smallholder farmers receive cows purchased by the company and then sell them back to the company at a guaranteed price or at a higher price they find in the market. Farmers keep 2/3 of the difference between the purchase and sale price, and the company keeps 1/3. This intervention is bundled with insurance to protect the farmer against cow death. Other possible services include subsidized high-quality feed and growth monitoring to increase the value of the cow. Women will be specifically targeted for contracts to increase their empowerment in a sphere where they are responsible for physical labor.